1991
DOI: 10.1002/neu.480220205
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical specificity in the co‐localization of aromatase and estrogen receptors

Abstract: The relative distributions of aromatase and of estrogen receptors were studied in the brain of the Japanese quail by a double-label immunocytochemical technique. Aromatase immunoreactive cells (ARO-ir) were found in the medial preoptic nucleus, in the septal region, and in a large cell cluster extending from the dorso-lateral aspect of the ventromedial nucleus of the hypothalamus to the tuber at the level of the nucleus inferioris hypothalami. Immunoreactive estrogen receptors (ER) were also found in each of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(59 citation statements)
references
References 53 publications
1
58
0
Order By: Relevance
“…In quail, estrogen is very potent in the male POM in up-regulating aromatase activity and the number of cells expressing aromatase . Somewhat surprisingly, aromatase is not co-localized with ER (usually antibodies specific to ERα) in areas such as the POM while in other areas such as the ventro-medial nucleus of the hypothalamus the co-localization is high [Balthazart et al, 1991;. This lack of co-localization is consistent with the hypothesis that aromatase is regulated trans-synaptically .…”
Section: The Preoptic Nucleus and Male Sexual Behavior In Japanese Quailsupporting
confidence: 69%
See 1 more Smart Citation
“…In quail, estrogen is very potent in the male POM in up-regulating aromatase activity and the number of cells expressing aromatase . Somewhat surprisingly, aromatase is not co-localized with ER (usually antibodies specific to ERα) in areas such as the POM while in other areas such as the ventro-medial nucleus of the hypothalamus the co-localization is high [Balthazart et al, 1991;. This lack of co-localization is consistent with the hypothesis that aromatase is regulated trans-synaptically .…”
Section: The Preoptic Nucleus and Male Sexual Behavior In Japanese Quailsupporting
confidence: 69%
“…In starlings, as was observed in quail, the highest levels of expression are apparent in the lateral part of the nucleus. This lateral part of the nucleus corresponds to where cells expressing aromatase are most abundent in the quail POM [Balthazart et al, 1990[Balthazart et al, , 1991. Darkfield photomicrographs illustrating the expression of ERβ, ERα, and AR in the song control nucleus, HVc (or High Vocal Center) and the preoptic medial nucleus (POM) in European starlings as determined by in situ hybridization histochemistry.…”
Section: Localization Of Estrogen Receptor ␣ and ␤ In The Brain Of Eumentioning
confidence: 99%
“…Aro-ir is present in neuronal cell bodies in the BNST and the MEA [58]. Moreover, colocalization of Aro-ir and ER-ir has only been demonstrated in quails [61] and musk shrew [62] and, in both species, Aro-ir and ER-ir are colocalized in relatively few medial preoptic neurons. Based on this evidence, any synergy between estrogen and androgen with respect to mating cannot be explained in terms of a single cell type.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the brain of the Japanese quail possesses cytochrome P450 side-chain cleavage enzyme (P450scc; gene name Cyp11a ), 3β-hydroxysteroid dehydrogenase/Δ 5 -Δ 4 -isomerase (3β-HSD; gene name Hsd3b ), 5β-reductase (gene name Srd5b ), cytochrome P450 17α-​hydroxylase/c17,20-lyase (P450 17α,lyase ; gene name Cyp17 ), 17β-hydroxysteroid dehydrogenase (17β-HSD; gene name Hsd17b ), etc., and produces pregnenolone, progesterone, epipregnanolone (3β,5β-tetrahydroprogesterone; 3β,5β-THP), androstenedione, testosterone, and estradiol-17β from cholesterol [2,6,19,20,21,22,23,24,25]. The expression and activity of cytochrome P450 aromatase (P450arom; gene name Cyp19 ), which converts testosterone into estradiol-17β, have also been demonstrated in the quail brain [54,55,56,57,58,59,60,61,62,63,64,65]. Independently, neurosteroidogenesis in the brain has been demonstrated in the zebra finch [27,28,29,30,31,32,33,34,35].…”
Section: Studies On Neurosteroidogenesis In Birdsmentioning
confidence: 99%